PRODUK JASA DOMPET DHUAFA: BERZAKAT TANPA KONTAK FISIK MELALUI WEBSITE - Aditya Nurrohma (INTELEKSIA - Jurnal Pengembangan Ilmu Dakwah, 2021)
Covid-19 pandemic has limited people from interacting directly for breaking the chain of Covid-19 transmission. Even, in the case of doing alms directly, people could potentially be exposed to the Covid-19 virus. One of online zakah services which can be used during this pandemic is the website of dompetdhuafa.org. It has received many awards and possesses various features to fulfil the needs of muzakki without physical contact. This study aims to describe online zakah service of dompetdhuafa.org by applying Christopher Lovelock’s service marketing theory perspective. It uses descriptive qualitative methods, with documentation as data collecting. It indicates that Dompet Dhuafa has a core product in the form of zakah distribution facility through its online service of dompetdhuafa.org. then in order to support this core product, Dompet Dhuafa provides services classified into 8 features consisting of information on zakah payment to Islamic information, easy order when doing zakah, billing an accurate amount of zakah, fast online website accessing consultation, hospitality and easy website access, muzakki’s personal data security, and exception in the form of complaint service.